2007
DOI: 10.1177/0269215507075495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an intensive rehabilitation programme on patients with Huntington's disease: a pilot study

Abstract: Intensive rehabilitation treatments may positively influence the maintenance of functional and motor performance in patients with Huntington's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 41 publications
7
103
1
4
Order By: Relevance
“…Whilst the intervention reported here did not appear to significantly impact on some aspects of executive function, significant improvements in memory and learning, task accuracy and cognitive processing speed of visual scanning and sequencing tasks were achieved over longitudinal timeframes. This contrasts with the Zinzi et al study, which demonstrated maintenance of baseline cognitive capacity, determined using the Mini Mental State Examination, after two years of intermittent rehabilitation in individuals with early-to-mid stage Huntington's disease 84 , and validates the use of a continuous program of intervention for provision of maximal benefits. Furthermore, Baker et al demonstrated improved executive function performance in women with amnestic mild cognitive impairment after six months of high-intensity aerobic exercise 161 , suggesting that optimising the program with provision of a greater aerobic component may provoke executive function improvement.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Whilst the intervention reported here did not appear to significantly impact on some aspects of executive function, significant improvements in memory and learning, task accuracy and cognitive processing speed of visual scanning and sequencing tasks were achieved over longitudinal timeframes. This contrasts with the Zinzi et al study, which demonstrated maintenance of baseline cognitive capacity, determined using the Mini Mental State Examination, after two years of intermittent rehabilitation in individuals with early-to-mid stage Huntington's disease 84 , and validates the use of a continuous program of intervention for provision of maximal benefits. Furthermore, Baker et al demonstrated improved executive function performance in women with amnestic mild cognitive impairment after six months of high-intensity aerobic exercise 161 , suggesting that optimising the program with provision of a greater aerobic component may provoke executive function improvement.…”
Section: Discussioncontrasting
confidence: 69%
“…Our inability to significantly impact on depression mimics that of the other multidisciplinary rehabilitation program provided to early-to-mid-stage patients with Huntington's disease 84 . Changes to behaviourial aspects during performance of everyday activities, as reported by carers/support people, indicates a trend towards increased behavioural problems after 9 months intervention, in contrast to maintenance of these levels after 18 months, suggesting a delayed response to the intervention consistent with that of the cognitive data.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Zinzi and colleagues demonstrated that an inpatient multidisciplinary rehabilitation approach lasting three weeks can improve function in mobility and activities of daily living. 5 Several studies have demonstrated the benefits of a physical therapy program incorporating posture, gait. and balance training for improving motor function.…”
Section: Introductionmentioning
confidence: 99%
“…and balance training for improving motor function. [5][6][7] Additionally, a home-based strengthening exercise program was shown to improve gait and balance when supervised by a family member or caregiver. 8 However, apathy, depression, motor problems, and inadequate transportation present exercise barriers.…”
Section: Introductionmentioning
confidence: 99%